Automating LCL Shipment Booking and Enhancing Customer Experience with AI - A Study on Process Efficiency and Digital Transformation in Logistics (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Recent changes in the global economy and the increase in digital technology, plus the customer's demand for better service and communication from the logistics provider, have driven rapid changes in the logistics industry. In this context, there is a growing reliance on Less than Container Load (LCL) consolidation services as they provide an economical way for multiple customers to share a shipping container. However, operational inefficiencies such as delays in booking, lack of communication, reliance on manual coordination of operations and difficulty with documentation still negatively impact service quality and customer satisfaction.The purpose of this research project was to determine the role of Automation (via Artificial Intelligence [AI]) in improving the efficiency of booking shipments for customers and ultimately improving the customer experience. The research involved an analysis of the various operational issues faced by logistics providers related to internal coordination and communication practices in the management of the consolidation-based logistics service process. The study involved administering a structured questionnaire to 50 respondents and using various statistical analysis methods such as percentage calculations, One-Way ANOVA, Independent samples t-tests and Chi-Square tests to evaluate the responses for the research purpose.Manual processes and the time it takes to coordinate work are the main causes for inefficiency in operations. Employees surveyed indicated they are generally aware of and accept the use of AI-based systems, such as automated booking and documentation management. The results show AI-driven process automation can increase operational efficiencies, reduce the time it takes to book shipments, increase the accuracy of communications, and increase customer satisfaction for logistics operations.